APLIKASI CHECKLIST SAFETY BERBASIS MOBILE MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) UNTUK AUDIT KESEHATAN DAN KESELAMATAN KERJA (K3) DI PT.MATAHARI PUTRA PRIMA,TBK - Muhamad Arno Yuli Saputra; Muhammad Nur Fadillah; Dedi Setiadi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractPT Matahari Putra Prima Tbk (MPPA) is an Indonesian retail company which is the owner of the Matahari Department Store and Hypermart Supermarkets and Foodmart networks. For more than 50 years, the company group PT Matahari Putra Prima Tbk (MPPA) has successfully developed Matahari Department Store, Matahari Supermarket and finally Matahari Market Place, which is a supermarket for the premium segment in Kelapa Gading, Bogor, Serpong, Metropolis and GTC in Makassar. Since November 2002, MPPA has also operated 46 Boston Drugs & Pharmacy stores in its supermarkets to support the concept of one stop shopping. However, behind all this, PT Matahari Putra Prima Tbk (MPPA) still has problems in the field of occupational health and safety (K3). This writing aims to identify, assess and provide recommendations for controlling the OSH risks that exist in PT Matahari Putra Prima Tbk (MPPA). The method used in this paper is Job Safety Analysis (JSA) based on mobile android. Data collection was carried out by means of observation, and distributing questionnaires.The results in this paper are able to analyze the need for a safety checklist with the Job Safety Analysis (JSA) method and the safety checklist application as an K3 audit tool in the PT. Matahari Putra Prima Tbk Â Keywords: Android; checklist; K3; JSA